New friends for Ago2 in neuronal plasticity. (29th July 2015) - Sananbenesi, Farahnaz; Fischer, Andre
<x xml:space="preserve">Abstract</x> MicroRNAs have emerged as central regulators of cellular homeostasis and increasing evidence suggests that they play a key role in neuronal plasticity. Major efforts are made to define microRNA networks and their targets in the brain. The mechanisms by which microRNA activity is regulated are, however, relatively unexplored. In this issue of The EMBO Journal, Störchel et al (2015) screened for proteins that affect microRNA function in neurons. They identify Nova1 and Ncoa3 as novel regulators of miRNA activity and demonstrate that both proteins are essential for neuronal plasticity in a microRNA‐dependent manner.